Distribution and abundance of Minnesota-breeding Ring-necked Ducks Aythya collaris - Zicus, Michael C; Rave, David P; Fieberg, John R; Giudice, John H; Wright, Robert G (Wildfowl, 2013)
Concerns about Ring-necked Duck Aythya collaris breeding numbers in Minnesota suggested a population survey was needed; however, knowledge of the species’ distribution and abundance was poor. Existing waterfowl survey data were used to define an aerial sampling frame, and a habitat model incorporating land-cover imagery was used to develop a survey to describe breeding pair distribution and abundance in 2004–2007. In 2004, a stratified random sample was used to estimate pair numbers for plots having moderate to high potential for breeding ducks, and a sensitivity analysis was used to estimate pair numbers for the remaining un-surveyed plots. Pairs occurred throughout the survey area, primarily on small (median = 8.3 ha) wetlands with open, bog-like margins, with greatest concentrations in the west. The 2004 estimate was of 20,000 breeding pairs, with sensitivity analysis suggesting that half of these occupied plots assumed to have few if any Ring-necked Ducks. Incomplete habitat model definitions and shortcomings in land-cover imagery contributed to stratification failure in 2004. Habitat definitions were refined and survey plots were re-stratified in 2005–2007. A second survey replaced the sensitivity analysis to better estimate pairs in plots assumed to have few ducks. Breeding pair estimates from both surveys combined were of 11,000–15,000 pairs in 2005–2007. Survey development is used to illustrate how an adaptive approach can better ensure survey success. By focusing first on development, shortcomings in the untested habitat model, land-cover imagery, and initial stratification were revealed and changes leading to more precise population estimates were made. Issues encountered in survey development likely typify those experienced when initiating large-scale monitoring efforts of little studied species.